Determination of critical state soil parameters - Wanchai Teparuksa; Ohta, Hideki; Yudhbir; Tomiolo, Andrea; KEIDANREN Foundation (Japan) (Bangkok : Asian Institute of Technology, 1982)
This investigation is aimed at finding a way of determining the critical state soil parameters. Due to practical and economic considerations this study is restricted to the use of well-established empirical correlations between soil properties as the basis of a comparison with the author' s own laboratory research. To achieve t his purpose, the research has been divided into the following two parts: (i) a check was made that there was no significant difference between the test results on samples taken by using rotary drilling and percussive wash boring, the latter method being widely used in Thailand, while on the other hand most of the empirical correlations have obtained from rotary drilling. Therefore, the previously established empirical correlations could be used. (ii) it is shown that some of the empirical correlations can assist in estimating critical state soil parameters within a certain degree of accuracy and with some limitations. Such conclusions make it possible to reduce the cost and time for estimating critical state soil parameters.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Soil mechanics